2017
DOI: 10.3201/eid2301.160631
|View full text |Cite
|
Sign up to set email alerts
|

Sequelae and Other Conditions in Ebola Virus Disease Survivors, Sierra Leone, 2015

Abstract: We rapidly assessed the health of Ebola virus disease (EVD) survivors in Kenema, Sierra Leone, by reviewing medical charts of all patients attending the Survivor Clinic of Kenema Government Hospital. Data were abstracted on signs and symptoms at every attendance. As of November 2015, a total of 621 attendances by 115 survivors with laboratory-confirmed EVD were made to the Survivor Clinic. Most (60.9%) survivors were women. Survivors’ median age was 28 years (range 0.25–70 years). Survivors attended the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 14 publications
0
15
1
1
Order By: Relevance
“…Our study indicates that close to a quarter (24.9%) of survivors exhibited a possible case of anxiety which is slightly higher than those reported by Nanyonga et al [ 31 ] and Mohamed et al [ 44 ] in Kenema, Eastern Sierra Leone. Although studies from East Africa [ 45 47 ] and in Guinea [ 28 ], Nigeria [ 48 ] Liberia [ 49 ] and within Sierra Leone [ 30 , 50 52 ] using quantitative and qualitative research designs have reported that psychological harm is common among Ebola survivors, it has failed to assess anxiety among Ebola survivors specifically, and this makes comparison among studies to be difficult.…”
Section: Discussioncontrasting
confidence: 66%
“…Our study indicates that close to a quarter (24.9%) of survivors exhibited a possible case of anxiety which is slightly higher than those reported by Nanyonga et al [ 31 ] and Mohamed et al [ 44 ] in Kenema, Eastern Sierra Leone. Although studies from East Africa [ 45 47 ] and in Guinea [ 28 ], Nigeria [ 48 ] Liberia [ 49 ] and within Sierra Leone [ 30 , 50 52 ] using quantitative and qualitative research designs have reported that psychological harm is common among Ebola survivors, it has failed to assess anxiety among Ebola survivors specifically, and this makes comparison among studies to be difficult.…”
Section: Discussioncontrasting
confidence: 66%
“…This may explain why a greater proportion of EVD survivors seen at ELWA experienced symptoms than the proportion reported in the Uganda study [3]. Other studies conducted during the 2014–2016 outbreak have similarly described high rates of musculoskeletal pain and headache [6–8, 26], suggesting that selection bias alone may not explain the high rates in our study.…”
Section: Discussionmentioning
confidence: 48%
“…It is now known at that approximately two-thirds of EVD survivors develop neurological complications and more than half experience ocular and musculoskeletal problems. [4] Similar investigations are being conducted in Sierra Leone[56] and in Guinea (funded by the French Ebola Task Force and the Institut de Recherche pour le Developpement). [7] With new discoveries, it its becoming increasingly evident that additional clinical, basic science, and epidemiological work will be required to ensure an in-depth understanding of EVD's pathophysiological sequelae.…”
mentioning
confidence: 99%